A social perspective on S-D logic - Nijboer, Johannes (2011)
This exploratory study seeks to enhance the understanding of co-creative variables in the context of Service-Dominant logic. Variables such as the integration of resources, operant resource development and C2C interaction have been examined in respect to current marketing literature by utilising the land house of Chatsworth as a case study. In addition, this research embraces a customer orientation to enhance the role of the customer in search for value.